Connecting social technologies with information literacy - Jones, Kara (2007)
Social technologies such as weblogs, wikis, and social bookmarking are emerging both as information resources and as tools for research. This paper reflects on these technologies and suggests they may be well placed to build fluency in the higher-order thinking skills outlined in various information literacy frameworks, particularly in an educational context. A high proportion of today’s learners are very comfortable with technology and Web 2.0 resources. The characteristics of the information they are accessing are also changing, bringing a stronger need for sophisticated evaluation and analysis skills. Where do social technologies fit within information literacy frameworks, and where can they be used in the day to day instruction of information skills? This paper suggests social technologies perform a dual role: they are not only useful sources of information but also resources to be used to develop ideas and research, using collaboration and community platforms with which learners today are familiar with. Librarians who provide information literacy instruction would benefit from an awareness of these tools and where they sit within today’s information environment.